2013
DOI: 10.1186/1757-2215-6-79
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the clinical potential for 14-3-3 zeta protein to serve as a biomarker for epithelial ovarian cancer

Abstract: ObjectiveRecently, 14-3-3 zeta protein was identified as a potential serum biomarker of epithelial ovarian cancer (EOC). The goal of this study was to investigate the clinical potential of 14-3-3 zeta protein for monitoring EOC progression compared with CA-125 and HE4.DesignProspective follow-up study.SettingUniversity of Pecs Medical Center Department of Obstetrics and Gynecology/Oncology (Pecs, Hungary).PopulationThirteen EOC patients with advanced stage (FIGO IIb-IIIc) epithelial ovarian cancer that underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Studies have shown that the 14-3-3zeta protein is overexpressed in a variety of tumor types, including HCC[29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the 14-3-3zeta protein is overexpressed in a variety of tumor types, including HCC[29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…The role of 14‐3‐3 ζ/δ in ovarian cancer is also controversial. Hatzipetros found that serum 14‐3‐3 zeta protein levels did not significantly differ in healthy postmenopausal patients versus epithelial ovarian cancer (EOC) patients . However, Kobayashi demonstrate that 14‐3‐3 zeta was secreted by ascitic monocytes/macrophages from EOC patients and was present in malignant ascites of EOC patients, but the functional role for 14‐3‐3 zeta as a secreted protein was unclear .…”
Section: Discussionmentioning
confidence: 99%
“…Hatzipetros found that serum 14-3-3 zeta protein levels did not significantly differ in healthy postmenopausal patients versus epithelial ovarian cancer (EOC) patients. (34) However, Kobayashi demonstrate that 14-3-3 zeta was secreted by ascitic monocytes ⁄ macrophages from EOC patients and was present in malignant ascites of EOC patients, but the functional role for 14-3-3 zeta as a secreted protein was unclear. (35) Waldemarson et al (2012) found a gradual upregulation of 14-3-3 f ⁄ d protein when going from normal to benign to borderline to malignant tumors using iTRAQ technology, making it a biomarker of early stage ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the 14-3-3ζ protein was identified as a potential serum biomarker of epithelial ovarian cancer [41, 42]. However, levels of the 14-3-3ζ protein were not found to be changed significantly as a consequence of treatment [43]. In this study, we use immunologic and molecular methods to test the possibility of 14-3-3ζ as a TAA and whether anti-14-3-3ζ antibody can be used as an early diagnostic biomarker in HCC patients.…”
Section: Discussionmentioning
confidence: 99%